Pulp and paper production from Spruce wood with kraft and modified kraft methods - Tutus, A.; Ates, S.; Deniz, I. (Academic Journals, 2010)
In this study, kraft and modified kraft pulping methods were applied for spruce (Picea orientalis) wood collected from the Black Sea Region of Turkey. Fiber properties, carbohydrate contents, strength and optical properties of resultant paper were included to determine the properties of these pulp samples. Optimum kraft, kraft-borohydride (NaBH4), kraft- anthraquinone (AQ) and kraft-ethanol pulping conditions were determined. After determining screened yield, kappa number, viscosity, fiber length, fiber coarseness, α-cellulose, holocellulose, lignin and ash content, breaking length, tear indexes and burst indexes of the obtained pulp samples, the differences of SEM image of each pulp sample were captured and evaluated. The results indicated that kraft-AQ pulps from spruce wood exhibited better characteristics than the other pulp samples with lower kappa number, higher paper strength properties and optical properties. However, kraft-NaBH4 method gave pulps with closer characteristics to kraft-AQ and also gave a higher screened yield and α-cellulose ratio than the others.
Keywords: Spruce, modified kraft methods, borohydride, AQ, SEM